2018
DOI: 10.1159/000488758
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Emotion on Second Formant Frequency Fluctuations in Adults Who Stutter

Abstract: Objective: Changes in second formant frequency fluctuations (FFF2) were examined in adults who stutter (AWS) and adults who do not stutter (ANS) when producing nonwords under varying emotional conditions. Methods: Ten AWS and 10 ANS viewed images selected from the International Affective Picture System representing dimensions of arousal (e.g., excited versus bored) and hedonic valence (e.g., happy versus sad). Immediately following picture presentation, participants produced a consonant-vowel + final /t/ (CVt)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…To facilitate the production of the vocally-expressed confidence, speakers were instructed to produce each sentence twice with a certain level of confidence by responding to the same question from a native Wuxi dialect female confederator in a mini-dialog format (e.g., Question: What is the word? Answer: This word is "X"; Jiang and Pell, 2014, 2018. The target vowel was the new information in the answer which corresponded to the wh-constituent in the questions, which aimed at inducing natural vowels for subsequent acoustic analysis (Waters et al, 2021).…”
Section: Recording and Elicitation Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…To facilitate the production of the vocally-expressed confidence, speakers were instructed to produce each sentence twice with a certain level of confidence by responding to the same question from a native Wuxi dialect female confederator in a mini-dialog format (e.g., Question: What is the word? Answer: This word is "X"; Jiang and Pell, 2014, 2018. The target vowel was the new information in the answer which corresponded to the wh-constituent in the questions, which aimed at inducing natural vowels for subsequent acoustic analysis (Waters et al, 2021).…”
Section: Recording and Elicitation Proceduresmentioning
confidence: 99%
“…According to the latter approach, the material was regrouped based on perception results, and the regrouped stimuli could only reflect what listeners' commitment but not speakers' own intention. Additionally, while in ideal cases, the speaker and the listener are convergent in the use of communicative cues, in many cases, such convergence is not reached and the encoding and the decoding processes seem to rely on a partially-independent set of cues (Jiang and Pell, 2016, 2018. In Brunswik's lens model (Brunswik, 1956), acoustic cues in the voice are understood by listeners as probabilistic and partly redundant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been speculated that changes in emotional processes may impact the planning and production (i.e., linguistic, cognitive, and speech-motor) processes that are necessary for fluent speech. Research in both young children 117 and adults who stutter [118][119][120][121] has demonstrated that emotion impacts their speech-motor processes to a greater degree than in similarly aged non-stuttering participants. This emerging research is important because it may lead to novel insights on the mechanisms by which emotional processes contribute to stuttering-advancing our understanding of the nature of stuttering and development of treatment approaches.…”
Section: Future Directionsmentioning
confidence: 99%
“…Many researchers have focused on the temporal (VOT, vowel duration, consonant closure time, etc.) and spectral (formant frequencies) aspects of stuttered events (Zebrowski, Conture, & Cudahy, 1985;Howell & Williams, 1992;Robb & Blomgren, 1997;Howell & Vause, 1986;Yaruss & Conture, 1993;Bauerly & Paxton, 2017;Bauerly, 2018;Bauerly, Jones, & Miller, 2019). Acoustic analysis can determine the laryngeal and supralaryngeal articulatory behavior of PWS.…”
Section: Acoustic Features and Stutteringmentioning
confidence: 99%